Efficient Preparation of O-Isopropylidene Derivatives of Carbohydrates Catalyzed by Sulfonated Graphene (GR-SO3H) as a Sustainable Acid Catalyst - Rabha, Padmashri; Panchadhayee, Rajib (Synthesis, 2023)
Sulfonated graphene (GR-SO3H) has emerged as a mild, efficient and sustainable catalyst for the preparation of O-isopropylidene derivatives of unprotected and anomeric-protected carbohydrates with acetone and 2,2-dimethoxypropane at room temperature. This methodology not only provides excellent yields but also reduces reaction times, and it demonstrates exceptional recyclability, allowing the catalyst to be reused multiple times.
Keywords: acetone; carbohydrates; 2,2-dimethoxypropane; GR-SO3H; O-isopropylidene acetals; sustainability